2011
DOI: 10.1007/s10608-011-9360-4
|View full text |Cite
|
Sign up to set email alerts
|

Obsessive Beliefs and Dimensions of Obsessive-Compulsive Disorder: An Examination of Specific Associations

Abstract: Although current cognitive-behavioral models have highlighted a central role of dysfunctional ''obsessive beliefs'' about threat, responsibility, uncertainty, perfectionism, importance and control of thoughts in the development of obsessive-compulsive disorder (OCD), empirical evidence in support of this notion has been inconsistent. The present investigation further examines the association between obsessive beliefs and OCD symptoms among nonclinical (Study 1) and clinical samples (Study 2). Findings from Stu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
21
0

Year Published

2012
2012
2019
2019

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 46 publications
(24 citation statements)
references
References 37 publications
3
21
0
Order By: Relevance
“…threat estimation, control of thoughts, tolerance of uncertainty, perfectionism) lie at the heart of the onset and maintenance of OCD symptoms (Jones, Mair, Riemann, Mugno, & McNally, 2018;McNally, Mair, Mugno, & Riemann, 2017;Tolin, 47 & Maltby, 2006). However such maladaptive beliefs have been shown to poorly differentiate between those with OCD and other anxiety diagnoses (Tolin et al, 2006;Viar, Bilsky, Armstrong, & Olatunji, 2011), leading some to propose that the obsessive component of OCD is reflective of anxiety (or indeed psychopathology) more generally (Tolin et al, 2006). Collectively the inconsistencies in clustering observed in our data indicate that it is particularly difficult to delineate the most common forms of internalizing psychopathology into clear and distinct disorder categories in childhood and adolescence.…”
Section: Discussionmentioning
confidence: 99%
“…threat estimation, control of thoughts, tolerance of uncertainty, perfectionism) lie at the heart of the onset and maintenance of OCD symptoms (Jones, Mair, Riemann, Mugno, & McNally, 2018;McNally, Mair, Mugno, & Riemann, 2017;Tolin, 47 & Maltby, 2006). However such maladaptive beliefs have been shown to poorly differentiate between those with OCD and other anxiety diagnoses (Tolin et al, 2006;Viar, Bilsky, Armstrong, & Olatunji, 2011), leading some to propose that the obsessive component of OCD is reflective of anxiety (or indeed psychopathology) more generally (Tolin et al, 2006). Collectively the inconsistencies in clustering observed in our data indicate that it is particularly difficult to delineate the most common forms of internalizing psychopathology into clear and distinct disorder categories in childhood and adolescence.…”
Section: Discussionmentioning
confidence: 99%
“…In studies with clinical samples, higher perfectionism/certainty beliefs were associated with greater symmetry symptoms (Calamari et al, 2006;Viar, Bilsky, Armstrong, & Olatunji, 2011;Wheaton, Abramowitz, Berman, Riemann, & Hale, 2010), ordering symptoms (Calleo, Hart, Björgvinsson, & Stanley, 2010;Tolin, Brady, & Hannan, 2008), hoarding and obsessing (Tolin et al, 2008), and checking behaviors (Julien, O'Connor, Aardema, & Todorov, 2006). Research using nonclinical samples demonstrated that perfectionism/certainty beliefs were associated with washing, checking, and ordering symptoms (Myers, Fisher, & Wells, 2008;Wu & Cortesi, 2009).…”
Section: Ocd Symptom Dimensions and Overall Perfectionismmentioning
confidence: 97%
“…Rheaume, & Aublet, 1997;Lopatka & Rachman,1995;Rassin, Merckelbach, Muris, & Spaan, 1999), other studies report inconsistent results regarding the relationship between OC beliefs and OC symptoms (Belloch, Morillo, & Garcia-Soriano, 2007;Myers, Fisher & Wells, 2008;Sica et al, 2004;Sica, Taylor, Arrindell, & Sanavio, 2006). For instance, a recent study failed to support the hypothesis that OCD patients endorse obsessive beliefs more strongly than patients with generalized anxiety disorder (Viar, Bilsky, Armstrong, & and Olatunji, 2011). Jó nsson, Hougaard, and Bennedsen (2011) investigated OC beliefs in the form of inflated responsibility (IR) and thought action fusion (TAF) as predictive and mediating variables in individual and group cognitive behavioral therapy outcome for obsessive compulsive disorder.…”
Section: Introductionmentioning
confidence: 99%